Guava seed and agro-industrial potential as a nutritional contribution in bakery products including circular economy - Ramírez, Verónica Marcela
The guava seeds (Psidium Guajava L) correspond to the main residue of the industrialization of this fruit, around 25% of the total weight of the fruit is discarded, being 8% the seeds, these do not have any type of subsequent treatment, causing not only an environmental impact given the high volumes, but also favor the growth of microorganisms and pests in the storage area; The red roll is an autochthonous and artisanal product very common in typical Colombian bakeries, obtained by mixing the basic ingredients and then baking it, adding guava paste. Objective: to evaluate the effect of the partial replacement of wheat flour by guava seed flour on the sensory characteristics of the guava roll type bread product.  A red roll was made according to the parameters established in the bakery workshop of SENA La Salada, later two treatments were made, control, F25, substituting part of the wheat flour for guava seed flour (HSG), determining their physicochemical characteristics, finally its sensory acceptance was evaluated with 30 untrained judges. Within the sensory analysis, marked differences were evidenced between the control and F25 treatments for the oral texture variable, in contrast to the values ​​obtained for the flavor attribute and crumb structure, in which no marked differences were obtained in the evaluation of the judges. Finally, a product with nutritional quality and sensory acceptability was obtained, which could promote the use of guava seed flour in traditional Colombian bakery preparations.